ANALISIS KESIAPAN PEMERINTAH DESA WANCIMEKAR MENUJU KONSEP SMART VILLAGE - Alifah, Naufa; Izzati, Nurul; Azijah, Dewi Noor (UNIVERSITAS STEKOM, 2024)
The concept of Smart Village or smart village is a process of adjustment and development experienced by people in rural areas so that they can generate benefits and balance between information technology and villagers so that they can solve problems in the area by using the potential of existing resources that are owned intelligently. Three important elements in a Smart Village that influence one another consist of smart government, smart environment and smart economy. Wancimekar Village in Karawang Regency is seen as one of the villages that is still going through developments towards a smart village, where the obstacle factors will be reviewed through the three elements of the Smart Village concept. This study intends to understand how big the development process of Wancimekar Village is towards a Smart Village. The method used is qualitative narrative with data collection techniques carried out through interviews, direct observation and documentation by related parties and conducting literature studies. The results of this study indicate that the village of Wancimekar is ready to move towards the smart village concept because it is supported by adequate resources. In the aspect of digitizing village services, this is already in the digital development stage, namely by establishing an official digital service page, although it is still in the development stage.